2020
DOI: 10.33448/rsd-v9i8.5620
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de internação hospitalar por úlcera venosa em adultos no Brasil, Rio Grande do Sul e Santa Maria: série histórica

Abstract: Objective: to analyze the historical series in the period from 2008 to 2018 of the prevalence of hospitalization for venous ulcers in adults in Brazil, in the State of Rio Grande do Sul and in the municipality of Santa Maria. Method: documentary epidemiological study, historical series of the prevalence of hospital admissions for venous ulcers in the last 10 years. Results: when comparing the three locations, it is evident that in the state of Rio Grande do Sul there is a higher prevalence of hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
1
1
0
5
Order By: Relevance
“…About the sociodemographic characteristics of the patients, the present research demonstrated that there was no significant percentage difference between the gender of the participants, being similar to the qualitative approach study developed with 18 people with VU, where there were nine participants of each gender, respectively 9 .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…About the sociodemographic characteristics of the patients, the present research demonstrated that there was no significant percentage difference between the gender of the participants, being similar to the qualitative approach study developed with 18 people with VU, where there were nine participants of each gender, respectively 9 .…”
Section: Discussionsupporting
confidence: 69%
“…Telenursing to patients with venous ulcers: guidelines provided and outcome of remote monitoring other investigations carried out in Brazil, in which most of the participants had only incomplete primary education or no instruction 9,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Com relação às características sociodemográficas dos pacientes, a presente pesquisa demonstrou que não houve diferença percentual significativa entre o sexo dos participantes, sendo semelhante ao estudo de abordagem qualitativa desenvolvido com 18 pessoas com UV, onde houve nove participantes de cada sexo, respectivamente 9 .…”
Section: Discussionunclassified
“…Telenfermagem a pacientes com úlceras venosas: orientações fornecidas e desfecho do monitoramento remoto qualidade de vida. Ainda com relação às características sociodemográficas dos pacientes com UV atendidos na Clínica de Enfermagem em Estomaterapia, foi possível constatar que a maioria dos pesquisados tinha o ensino fundamental completo ou médio incompleto, divergindo de outras investigações realizadas no Brasil, nos quais a maior parte dos participantes possuía apenas o ensino fundamental incompleto ou nenhuma instrução 9,11 .…”
Section: Discussionunclassified
“…Estima-se que 3% da população brasileira apresentam a lesão, sendo que pessoas com diagnóstico de Diabetes Mellitus podem desenvolver maiores lesões (18) . Dessa forma, alcançar o objetivo da cicatrização da UV e tratar do usuário portador configuram consideráveis desafios de cuidado (19) .…”
Section: Introductionunclassified